2017
DOI: 10.1038/srep44326
|View full text |Cite
|
Sign up to set email alerts
|

Rare-metal-free high-performance Ga-Sn-O thin film transistor

Abstract: Oxide semiconductors have been investigated as channel layers for thin film transistors (TFTs) which enable next-generation devices such as high-resolution liquid crystal displays (LCDs), organic light emitting diode (OLED) displays, flexible electronics, and innovative devices. Here, high-performance and stable Ga-Sn-O (GTO) TFTs were demonstrated for the first time without the use of rare metals such as In. The GTO thin films were deposited using radiofrequency (RF) magnetron sputtering. A high field effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…5b and 5c). In the PBS test, the V th positively shifts by~6.6 V which is larger than that of sputtered GTO-TFTs under the same stress time [19]. We can observe a slightly decreased SS with the extension of time because more interface states…”
Section: Thin Film and Device Characterizationmentioning
confidence: 79%
See 1 more Smart Citation
“…5b and 5c). In the PBS test, the V th positively shifts by~6.6 V which is larger than that of sputtered GTO-TFTs under the same stress time [19]. We can observe a slightly decreased SS with the extension of time because more interface states…”
Section: Thin Film and Device Characterizationmentioning
confidence: 79%
“…In the previous reports [17,18], Ga is an oxygen vacancy inhibitor and can weaken the crystallinity of films. Recently, Matsuda et al [19] reported RF magnetron sputtered a-GaSnO (GTO)-TFTs with high mobility of 25.6 cm 2 V −1 s −1 at 350°C. Zhang et al [20] reported nanocrystalline Ga-rich GTO-TFTs with mobility of 1.03 cm 2 V −1 s −1 at 900°C.…”
Section: Introductionmentioning
confidence: 99%
“…An ITZO/IGZO bilayer structure is desirable for achieving high TFT performance because of the 2DEG layer formation at the heterointerface and high electron mobility of ITZO film resulting from partially substituting Sn 4+ for In 3+ . However, it is challenging to simultaneously obtain high mobility/on‐current and low off‐current in planar‐type heterojunction TFT devices .…”
Section: Electrical Properties Of the Indicated Mo Tfts (The Values Amentioning
confidence: 99%
“…We could explain crystallization of thin films in magnetic fields by the effect of ground vs excited states of metals, or by valence electron ordering. However, these two approaches were chosen based on the formation of metal ions in liquids and alloys [37] and the size of atom/ion/molecule effect [38]. Aluminium belongs to the boron group and, therefore, has three electrons in the last orbital with valence configuration ns 2 np 1 .…”
Section: Discussionmentioning
confidence: 99%